2020
DOI: 10.1002/anie.202010577
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Vanadium Oxides for Energy Conversion and Energy Storage: Current Trends and Emerging Opportunities

Abstract: Molecular vanadium oxides, or polyoxovanadates (POVs), have recently emerged as a new class of molecular energy conversion/storage materials, which combine diverse, chemically tunable redox behavior and reversible multielectron storage capabilities. This Review explores current challenges, major breakthroughs, and future opportunities in the use of POVs for energy conversion and storage. The reactivity, advantages, and limitations of POVs are explored, with a focus on their use in lithium and post‐lithium‐ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 146 publications
(372 reference statements)
0
86
0
4
Order By: Relevance
“…However, the outlook of POV chemistry is not limited to studies of atomic precision in materials science; indeed these cluster complexes have demonstrated themselves as valuable in a variety of fundamental and applications-based research. 53,98,101,102,169 Further advances in POV chemistry will seek to better understand how the properties of the metal oxide core can be manipulated toward a particular purpose. For example, understanding the precise mechanisms by which different POVs are formed is a critical step towards the purposeful generation of targeted core structures with desired features.…”
Section: Resultsmentioning
confidence: 99%
“…However, the outlook of POV chemistry is not limited to studies of atomic precision in materials science; indeed these cluster complexes have demonstrated themselves as valuable in a variety of fundamental and applications-based research. 53,98,101,102,169 Further advances in POV chemistry will seek to better understand how the properties of the metal oxide core can be manipulated toward a particular purpose. For example, understanding the precise mechanisms by which different POVs are formed is a critical step towards the purposeful generation of targeted core structures with desired features.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1‐4 ] POVs, a unique subclass of polyoxometalates (POMs), can be precisely designed with tunable structural diversity and unmatched range of structural features, sizes, and chemical physical properties. [ 5‐6 ] As an important class of POVs, decavanadate‐based POVs with well‐defined structures, redox properties and high negative charge could provide decent opportunities to combine with metal‐organic complexes and form the single component bimetallic POVs species with multi‐functionality. [ 7‐8 ] Therefore, decavanadates are especially attractive and considered to be remarkable building blocks to construct POVs‐based metal organic‐inorganic hybrids.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The chemistry could be further enhanced by e. g. decoration of the cluster anions by transition metal complexes [8–16] or by integration of transition metal cations into the cluster shell [17,18] . The latter cluster modification was also reported for a variety of POVs [19] . In compounds, which are chemically modified by transition metal cations or decorated by transition metal complexes, late transition metals were used in the syntheses or preformed complexes were applied.…”
Section: Introductionmentioning
confidence: 94%